The Role of Budget Decision Making as A Mediation of Accounting Information Systems and Organizational Culture on The Performance of Government Agencies - Setyani Setyani; Imam Abu Hanifah; Iis Ismawati Ismawati (PT. EQUATOR SINAR AKADEMIA, 2022)
This research aims to analyze the role of budget decision making as a mediation of accounting information systems and organizational culture on the performance of government agencies. This research uses a survey method with a questionnaire instrument to collect data. Data collection in this research was carried out by distributing questionnaires to respondents directly.The results of this research indicate that first, the accounting information system has no effect on the performance of government agencies. Second, organizational culture has a significant positive effect on the performance of government agencies. Third, the accounting information system has a significant positive effect on budget decision making. Fourth, organizational culture has a significant positive effect on budget decision making. Fifth, budget decision making has a significant positive effect on the performance of government agencies. Sixth, budget decision making is not mediated the relationship of accounting information systems to the performance of government agencies. Seventh, budget decision making mediated the relationship between organizational culture and the performance of government agencies.